Severe foreskin adhesion and meatal stenosis – complications after Circumcision: A Case Report - Khalilullah, Said Alfin; Ismy, Jufriady (Journal of International Surgery and Clinical Medicine, 2023)
Introduction: Although circumcision is the most common surgical surgery performed on newborn males, problems can still occur regardless of the technique utilized by the operator. Case description: This case report aims to highlight the case of a 13-year-old boy who presented with severe foreskin adhesion and meatal stenosis after circumcision and underwent surgical reconstruction. During surgery, the foreskin firmly bonds to the glans and cannot be scraped away. Even the glans penis is injured when released abruptly. The glans penis was then clearly visible and could be distinguished between the skin and glans penis after a circumferential incision was performed on the penis skin above the coronary sulcus. Adhesiolysis was then conducted from the proximal to the distal wound. After that, the meatoplasty was performed. Conclusion: Since issues related to complications of circumcision continue to emerge, it is important to have a proper understanding of the circumcision procedure and how to manage the complication. To our knowledge, this is the new insight into managing severe foreskin adhesion with a good outcome.